Enhancing the efficiency of PVDF-based piezoelectric catalysis through water-induced polarization and a micro-nano-composite strategy - Li, Haitao (2025)
Polyvinylidene fluoride (PVDF)-based piezoelectric catalysts show promise in mechanical force-driven catalysis due to their good biocompatibility, flexibility, and ease of fabrication. However, the catalytic activity of pristine PVDF is limited due to its low piezoelectric phase content (<20%), poor orientation, and low surface carrier concentration. Here, we introduce an efficient PVDF-based composite nano-catalyst (rGO/PVDF) with high piezoelectric catalytic performance. We achieve this by employing a composite strategy that combines nanoscale water-induced polarization with polar functional group-modified graphene (rGO) serving as a nanoelectrode. The nanoscale water polarization effect, together with the two-dimensional planar structure of PVDF and the modified graphene's polar functional groups, effectively induces orientation in the PVDF piezoelectric phase to increase the functional β phase content. As a result, the β phase content and crystallinity of rGO/PVDF reach 95% and 40%, respectively, which are 600% and 170% higher compared to those of pristine PVDF. This enhancement plays a crucial role in endowing the material with strong force-to-electricity conversion characteristics. Additionally, the surface-modified rGO also boosts PVDF's surface carrier concentration and provides active sites for catalysis on the rGO/PVDF composite. Notably, under optimized conditions, our catalyst achieves a ∼99.1% degradation rate of organic pollutants (10 mg L-1) after 12 minutes of sonication at 240 W and maintains a high efficiency of ∼93.7% even at a 10 times higher pollutant concentration (100 mg L-1). Our piezoelectric catalyst also demonstrates efficient H2O2 production at 95.8 mmol grGO-1 h-1, which is ∼9-fold and ∼134-fold higher than those of untreated PVDF and previously reported PVDF-based piezoelectric catalysts, respectively. This work paves the way for the development of highly efficient PVDF-based piezoelectric catalysts, thereby offering valuable insights for the advancement of mechanically driven catalysis in the environmental, energy, and chemical sectors.